Stochastic dilution effects weaken deterministic effects of niche‐based processes in species rich forests. Issue 2 (7th March 2016) - Wang, Xugao; Wiegand, Thorsten; Kraft, Nathan J. B.; Swenson, Nathan G.; Davies, Stuart J.; Hao, Zhanqing; Howe, Robert; Lin, Yiching; Ma, Keping; Mi, Xiangcheng; Su, Sheng‐Hsin; Sun, I‐Fang; et al.
Abstract: Recent theory predicts that stochastic dilution effects may result in species‐rich communities with statistically independent species spatial distributions, even if the underlying ecological processes structuring the community are driven by deterministic niche differences. Stochastic dilution is a consequence of the stochastic geometry of biodiversity where the identities of the nearest neighbors of individuals of a given species are largely unpredictable. Under such circumstances, the outcome of deterministic species interactions may vary greatly among individuals of a given species. Consequently, nonrandom patterns in the biotic neighborhoods of species, which might be expected from coexistence or community assembly theory (e.g., individuals of a given species are neighbored by phylogenetically similar species), are weakened or do not emerge, resulting in statistical independence of species spatial distributions. We used data on phylogenetic and functional similarity of tree species in five large forest dynamics plots located across a gradient of species richness to test predictions of the stochastic dilution hypothesis. To quantify the biotic neighborhood of a focal species we used the mean phylogenetic (or functional) dissimilarity of the individuals of the focal species to all species within a local neighborhood. We then compared the biotic neighborhood of species to predictions from stochastic null models to test if a focal species was surrounded by more or less similar species than expected by chance. The proportions of focal species that showed spatial independence with respect to their biotic neighborhoods increased with total species richness. Locally dominant, high‐abundance species were more likely to be surrounded by species that were statistically more similar or more dissimilar than expected by chance. Our results suggest that stochasticity may play a stronger role in shaping the spatial structure of species rich tropical forest communities than it does in species poorer forests. These findings represent an important step towards understanding the factors that govern the spatial configuration of local biotic communities. The stochastic dilution effect is a simple geometric mechanism that can explain why species' spatial distributions in species‐rich communities approximate independence from their biotic neighborhood, even if deterministic niche processes are in effect.